2017
DOI: 10.1039/c7cc08037a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic double hydroarylation of alkynes to 9,9-disubstituted 9,10-dihydroacridine derivatives by an electrophilic phenoxyphosphonium dication

Abstract: The electrophilic pyridinium-substituted phenoxy-phosphonium dicationic salt [(PhO)P(2-(N-Mepy))Ph][B(CF)], is shown to be an effective catalyst for the double hydroarylation of alkynes with diarylamines to afford a series of 9-methyl-9-aryl-9,10-dihydroacridine and 9,10-dimethyl-9-aryl-9,10-dihydroacridine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The reactivity of FLPs was extended to a growing range of small molecules, prompting a variety of other forms of metal-free catalysis. 31 For example, a wide variety of p-block FLPs have been exploited for transfer hydrogenations, [32][33][34] hydroborations, [35][36][37][38][39][40][41] C-H borylations, [42][43][44][45][46] hydroarylations, [47][48][49] and aminations, 50 as well as enantioselective a-aminations and Mannich-type reactions. [51][52][53][54] FLPs have also proved effective catalysts for polymerization 55 of a variety of acrylates, lactones, cyanamides, vinyl monomers, conjugated polar alkenes, and acrylamide monomers.…”
mentioning
confidence: 99%
“…The reactivity of FLPs was extended to a growing range of small molecules, prompting a variety of other forms of metal-free catalysis. 31 For example, a wide variety of p-block FLPs have been exploited for transfer hydrogenations, [32][33][34] hydroborations, [35][36][37][38][39][40][41] C-H borylations, [42][43][44][45][46] hydroarylations, [47][48][49] and aminations, 50 as well as enantioselective a-aminations and Mannich-type reactions. [51][52][53][54] FLPs have also proved effective catalysts for polymerization 55 of a variety of acrylates, lactones, cyanamides, vinyl monomers, conjugated polar alkenes, and acrylamide monomers.…”
mentioning
confidence: 99%
“…It should be noted that the groups of Stephan and Erker previously demonstrated that the use of frustrated Lewis pairs (FLPs) of sterically hindered anilines with the Lewis-acidic B­(C 6 F 5 ) 3 leads mainly to the formation of hydroaminated products . Later, Stephan and others improved this stoichiometric protocol into a catalytic process to achieve the hydroamination and hydroarylation of alkynes . Herein, we disclose a highly regioselective hydroarylation of conjugated dienes catalyzed by B­(C 6 F 5 ) 3 exclusively at the aryl para-position, affording wide variants of hydroarylated products under mild conditions.…”
mentioning
confidence: 99%
“…[2] Subsequently,w es howed that electrophilic phosphonium cations [3] were highly effective Lewis acids.W hile such species could be used as the Lewis acid component for FLP hydrogenation catalysis,t hey also proved useful for ab road range of reactions,i ncluding hydrodefluorination, [3a] dehydrocoupling,p seudo-transfer hydrogenation, [4] hydrosilylation, [5] functionalization of CF and CF 3 fragments, [6] and hydroarylation. [7] Other researchers have similarly broadened FLP chemistry to include C-, Si-and Sn-based Lewis acid species, [8] and we have also explored the potential of S-based Lewis acids. [9] Recently,weand others have turned our attention to the potential of nitrogen-based Lewis acids.Although N-containing compounds are usually considered basic due to the typical presence of alone pair of electrons,afew classes of nitrogen compounds are known to be N-centered electrophiles (Figure 1).…”
mentioning
confidence: 99%